Ein Betreuer macht mit den Kindern Turnübungen; im Vordergrund steht ein Hund
soziale Fragen;Familie (allgemein);Familie (speziell);Eltern;Waise soziale Fragen;sozialer Schutz;Sozialpolitik;Kinderbetreuung